Teaching Subtitling in the Classroom - Alvin Taufik (Journal of English Language and Culture, 2020)
One of the problems translators have regarding their job is text subtitling. Things to consider when creating a subtitle is not only changing an SL (source language) to a TL (target language), but also the linguistic dimension of subtitling and technical dimension of subtitling. In translation classes, these two dimensions should be taught so that the students are knowledgeable of creating a subtitle. This paper discusses how the two dimensions should be taught in the class and the implementation of the two dimensions in subtitling lesson in the classroom.